İlaç taşıyıcı sistem uygulamaları için grafen esaslı malzemeler üretilmesi - Demirhan, Kibar (My University, 2020)
1. ÖZETİlaç taşıyıcı sistem uygulamaları için grafen esaslı malzemeler üretilmesiÖğrencinin Adı: Kibar DEMİRHANDanışman Adı: Doç. Dr. Elif ÇALIŞKAN SALİHİAmaç: Grafen esaslı malzemeler farmasötik endüstrisinin pek çok uygulamasında kullanılabilecek eşsiz alternatiflerdir ve bu alanda büyük bir potansiyel taşırlar. Bu bağlamda, bu tez çalışmasının amacı ilaç taşıyıcı sistem uygulamaları için grafen esaslı malzemeler üretilmesidir. Gereç ve Yöntem: Grafen esaslı malzemeler grafen oksitin (GO) basit, kullanımı kolay ve yeşil bir yöntem ile modifikasyonu yoluyla üretilmiştir. Modifikasyon işlemi doğal maddeler olan sinnamaldehit (CA) ve undesilenik asit (UA) kullanılarak yapılmıştır. GO, laboratuvarımızda modifiye edilmiş Hummers yöntemi kullanılarak üretilmiştir. Bu yöntem grafitin kuvvetli yükseltgeyiciler ve asit karışımı ile okside edilmesi ve tabakalarının ayrıştırılmasına dayanır. Modifiye edilmiş GO numuneleri ise GO dispersiyonlarının reaktif çözeltileri ile karıştırılması ile üretilmiştir. Modifikasyon deneyleri çeşitli sıcaklıklar ve farklı deney süreleri kullanılarak tekrarlanmıştır. Yıkanan numuneler daha sonra etüvde kurutulmuştur. Numunelerin karakterizasyonu elektron mikroskopisi ve spektrofotometrik yöntemler kullanılarak yapılmıştır. Bulgular: Sonuçlar GO’nun CA ile başarılı olarak indirgendiğini göstermektedir. Bununla birlikte UA ise, GO’nun hem indirgenmesi hem de biyofonksiyonelleştirilmesi için etkili olmuştur. İndirgenmenin gerçekleştiği optimum koşullar tespit edilmiş ve grafen esaslı malzemelerin üretilmesi için bu koşullar kullanılmıştır. Üretilen yeni grafen esaslı malzemeler UV-Görünür alan spektroskopisi, FTIR spektroskopisi, Raman spektroskopisi, XRD analizi ve Taramalı elektron mikroskobu ile karakterize edilmiştir. Malzemelerin biyouyumluluk düzeyleri sitotoksisite testleri ile değerlendirilmiştir.Sonuç: GO’nun kimyasal indirgenmesi grafenin büyük miktarlarda üretimi için önemlidir çünkü kimyasal indirgeme büyük miktarlarda grafen üretimi için en işlevsel yöntemdir. GO’nun indirgenmesi için literatürde birçok indirgeyici bulunmaktadır fakat bunların çoğu canlılar için zararlıdır. Sonuç olarak, grafen ve grafen esaslı malzemelerin üretimi için ölçeklenebilir, kolay ve çevre dostu bir yönteme ihtiyaç vardır. Bu çalışma, grafen oksitin bazik ortam ya da ilave kimyasallar kullanılmadan modifiye edilmesi için yeşil bir yöntem önermektedir. Bu yöntemle üretilen grafen esaslı malzemeler biyomalzeme üretimi için bir alternatif sunmaktadır. Anahtar Sözcükler: Grafen oksit, sinnamaldehit, undesilenik asit, indirgenme, biyofonksiyonelleştirme.

2. SUMMARYProduction of graphene based materials for drug delivery applicationsName of the Student: Kibar DEMİRHANName of Supervisor: Assoc. Prof. Elif ÇALIŞKAN SALİHİObjective: Graphene based materials are excellent candidates and have great potential for many applications related to pharmaceutical industry due to their extraordinary and advanced properties. Therefore, the objective of this thesis was to produce graphene based materials for drug delivery applications. Material and Methods: Graphene based materials were produced via modification of graphene oxide (GO) using a simple, easy to handle and green method. Modification was done by using cinnamaldehyde (CA) and undecylenic acid (UA) as natural substances. GO was produced by using Hummers method which has been revised in our laboratory. This method consists of the exfoliation of graphite by the oxidation of it with strong oxidants and an acid mixture. Modified GO samples were thereafter prepared by mixing GO dispersions with reagent solutions. Modification experiments were repeated for selected temperatures during selected contact times. Washed samples were then dried in an oven. Sample characterization was done by using electron microscopy and spectrophotometric techniques. Results: Results of this thesis confirmed the succesful reduction of GO by CA. In addition to this, UA was effective for the reduction of GO besides biofunctionalization. Optimum conditions for the modification were found and used to produce graphene based materials. New graphene based materials produced were characterized using UV-Visible spectroscopy, FTIR spectroscopy, Raman spectroscopy, XRD analysis and Scanning electron microscope. Cytotoxicity tests were done to evaluate the biocompatibility of the materials.Conclusion: Chemical reduction techniques are important for the large-scale production of graphene since the chemical reduction is the most versatile method. There are several reducing agents reported for GO but these agents are mostly poisonous for the living organisms. So, there is a real need for a method that is scalable, easy to handle and environmentally friendly for the production of graphene and graphene based materials. The procedure used in this thesis offers a basic and green method for the production of graphene based materials which does not include using alcaline medium or any additives. Graphene based materials produced using this method are potential alternatives for the production of biomaterials.2. SUMMARYProduction of graphene based materials for drug delivery applicationsName of the Student: Kibar DEMİRHANName of Supervisor: Assoc. Prof. Elif ÇALIŞKAN SALİHİObjective: Graphene based materials are excellent candidates and have great potential for many applications related to pharmaceutical industry due to their extraordinary and advanced properties. Therefore, the objective of this thesis was to produce graphene based materials for drug delivery applications. Material and Methods: Graphene based materials were produced via modification of graphene oxide (GO) using a simple, easy to handle and green method. Modification was done by using cinnamaldehyde (CA) and undecylenic acid (UA) as natural substances. GO was produced by using Hummers method which has been revised in our laboratory. This method consists of the exfoliation of graphite by the oxidation of it with strong oxidants and an acid mixture. Modified GO samples were thereafter prepared by mixing GO dispersions with reagent solutions. Modification experiments were repeated for selected temperatures during selected contact times. Washed samples were then dried in an oven. Sample characterization was done by using electron microscopy and spectrophotometric techniques. Results: Results of this thesis confirmed the succesful reduction of GO by CA. In addition to this, UA was effective for the reduction of GO besides biofunctionalization. Optimum conditions for the modification were found and used to produce graphene based materials. New graphene based materials produced were characterized using UV-Visible spectroscopy, FTIR spectroscopy, Raman spectroscopy, XRD analysis and Scanning electron microscope. Cytotoxicity tests were done to evaluate the biocompatibility of the materials.Conclusion: Chemical reduction techniques are important for the large-scale production of graphene since the chemical reduction is the most versatile method. There are several reducing agents reported for GO but these agents are mostly poisonous for the living organisms. So, there is a real need for a method that is scalable, easy to handle and environmentally friendly for the production of graphene and graphene based materials. The procedure used in this thesis offers a basic and green method for the production of graphene based materials which does not include using alcaline medium or any additives. Graphene based materials produced using this method are potential alternatives for the production of biomaterials.Graphene oxide, cinnamaldehyde, undecylenic acid, reduction, biofunctionalization.
Keywords: biofunctionalization; biyofonksiyonelleştirme; cinnamaldehyde; Eczacılık; Grafen oksit; Graphene oxide; Health; indirgenme; Pharmacy; reduction; Sağlık; sinnamaldehit; undecylenic acid; undesilenik asit